A HISTOMORPHOMETRIC EVALUATION OF THE EFFECTS OF PLATELET-RICH FIBRIN AND RIFAMYCIN IN COMBINATION WITH AN ALLOGRAFT ON BONE AUGMENTATION WITH SIMULTANEOUS IMPLANT PLACEMENT IN RABBIT TIBIA - İlker Özeç; Sancar Şimşek; Emre Benlidayı; Mehmet Kürkçü (Cumhuriyet University, 2017)
Objective: To evaluate the potential of platelet-rich fibrin (PRF) and rifamycin to enhance guided bone augmentation with simultaneous high-profile dental implant placement in a rabbit tibia model. Materials and Methods: Dental implants protruding 2 mm were covered with dome-shaped stiff occlusive titanium barriers filled with demineralized freeze-dried bone allograft (DFDBA)+saline (7 rabbits), DFDBA + rifamycin (8 rabbits), or DFDB +PRF (8 rabbits). After 4 weeks, the animals were sacrificed, and undecalcified histomorphometric examination with toluidine blue staining was performed. Results: The bone-to-implant contact (BIC) was 58.43 ± 1.92% in the saline group, 68.3 ±20.37% in the rifamycin group, and 80.70±2.55% in the PRF group, and the percentage of new bone formation was 36.90 ± 0.94%, 45.26±0.60%, and 51.82±0.82%, respectively. Conclusions: Both PRF and rifamycin have potential to enhance GBA, and using DFDBA + PRF or DFDBA+rifamycin beneath a stiff occlusive titanium barrier next to a high-profile implant may enhance both BIC and new bone formation. Keywords: Guided bone augmentation, platelet-rich fibrin, rifamycin, allograft, high-profile dental implants